Control of Synanthedon (Aegeria) myopaeformis by Mating Disruption Using Sex Pheromone Dispensers in Northern Greece - Kyparissoudas, D.S.; Tsourgianni, Α. (ENTOMOLOGIA HELLENICA, 1993)
In 3 successive years (1990-1992) polyethylene tube dispensers, each containing 50.5 mg synthetic sex pheromone of the apple clearwing moth, Synanthedon (Aegeria) myopaeformis Borkh., were placed at a density of 680 per ha, once a year, in two adjacent commercial apple orchards each I ha in size. The degree of confusion reached almost 100% by releasing about 6 mg/ha/h, whereas the number of mated females decreased by 72.86%, compared with the untreated orchard. In 1993, after 3 years of experiments, a reduction of up to 91% of empty pupal skins per tree was attained. The encouraging results, especially when taking into account the relatively small size of the orchards, opens opportunities for the integrated control of this apple insect pest under the conditions of Northern Greece.